Retailer-Supplier Flexible Commitments Contracts: A Robust Optimization Approach - Ben-Tal, Aharon; Golany, Boaz; Nemirovski, Arkadi; Vial, Jean-Philippe (Manufacturing and Service Operations Management, 2005)
We propose the use of robust optimization (RO) as a powerful methodology for multiperiod stochastic operations management problems. In particular, we study a two-echelon multiperiod supply chain problem, known as the retailer-supplier flexible commitment (RSFC) problem with uncertain demand that is only known to reside in some uncertainty set. We adopt a min-max criterion, whereby the cost function is minimized against the worst case demand occurrence. To solve the min-max RSFC problem we employ a recent extension of the RO method adapted to dynamic decision problems and known as the affinely adjustable robust counterpart (AARC) methodology. The AARC solution is tested by a large simulation study and found to provide excellent results.